PHYSICAL AND MECHANICAL PROPERTIES OF POTATO CULTURE (Academicia Globe: Inderscience Research, 2021)
The article presents the results of the conducted experimental research on the study of the physical and mechanical properties of the potato culture, which is of great importance for the correct and reasonable design and calculation of working bodies and machines for the mechanization of their cultivation and harvesting, including potatoes.